DERIVATION OF DIFFERENTIAL EQUATIONS FOR SPINDLE OSCILLATION IN A SYSTEM OF RECTANGULAR COORDINATES - Isomiddinov, Anvarjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article develops mathematical models for the deformation of structural elements such as rods under spatially dynamic loading. The resulting vibration equations are described by systems of second-order partial differential equations with natural boundary and initial conditions.